Small business orientation and business growth of SMEs in growing market: Quantitative analysis of the lodging industries in Kyoto during the period of growing inbound tourists - Akiko YAMAMOTO; Naoki WAKABAYASHI (AAOS Transactions)
To determine how small business orientation affects firm performance, this study analyzed and examined lodging businesses in Kyoto during a period of rapid growth in tourism demand from the perspective of small business orientation. The results showed that the growth of sales relative to the growth rate of the number of employees was suppressive when the number of years of operation was long. This suggests that managers who have small business orientation may avoid labor intensification of their employees even during periods of increased demand when the amount of work increases.